Evidence of activation of vagal afferents by non-invasive vagus nerve stimulation: An electrophysiological study in healthy volunteers. (November 2017) - Nonis, Romain; D'Ostilio, Kevin; Schoenen, Jean; Magis, Delphine
Background: Benefits of cervical non-invasive vagus nerve stimulation (nVNS) devices have been shown in episodic cluster headache and preliminarily suggested in migraine, but direct evidence of vagus nerve activation using such devices is lacking. Vagal somatosensory evoked potentials (vSEPs) associated with vagal afferent activation have been reported for invasive vagus nerve stimulation (iVNS) and non-invasive auricular vagal stimulation. Here, we aimed to show and characterise vSEPs for cervical nVNS. Methods: vSEPs were recorded for 12 healthy volunteers who received nVNS over the cervical vagus nerve, bipolar electrode/DS7A stimulation over the inner tragus, and nVNS over the sternocleidomastoid (SCM) muscle. We measured peak-to-peak amplitudes (P1-N1), wave latencies, and N1 area under the curve. Results: P1-N1 vSEPs were observed for cervical nVNS (11/12) and auricular stimulation (9/12), with latencies similar to those described previously, whereas SCM stimulation revealed only a muscle artefact with a much longer latency. A dose-response analysis showed that cervical nVNS elicited a clear vSEP response in more than 80% of the participants using an intensity of 15 V. Conclusion: Cervical nVNS can activate vagal afferent fibres, as evidenced by the recording of far-field vSEPs similar to those seen with iVNS and non-invasive auricular stimulation.